PERAN KELOMPOK TANI DALAM PENINGKATAN PRODUKTIVITAS USAHATANI PADI SAWAH DI KABUPATEN BOMBANA - Arfiani, Arfiani (Jurusan Penyuluhan Pertanian FP UHO, 2025)
Farmer groups function as (1) a learning vehicle; (2) Cooperation Vehicle; and (3) Production units play an important role in agricultural development. This research aims to find out the role of farmer groups in increasing the productivity of rice farming. The research method used was a survey of farmer members of farmer groups in Bombana Regency using proportionate random sampling technique. The relationship between learning class and productivity obtained a Spearman rank correlation value which was moderately positive and significant, meaning that the more the role of farmer groups as a farming production unit increases, the more productivity of lowland rice farming will increase. The relationship between farming production units and productivity has a Spearman rank correlation value which has a strong and significant positive relationship, meaning that the more the group's role as a vehicle for cooperation increases, the more productivity will increase. The relationship between the role of farmer groups and productivity has obtained a Spearman rank correlation value which has a strong and significant positive relationship, meaning that as the role of the farmer group as a whole increases, the productivity of the group members' farming will also increase.